Does Kinesiophobia Affect Spatiotemporal Parameters in Patients with Ankylosing Spondylitis? - Deniz, Gulnihal; Bilek, Furkan; Yentur, Songul Baglan; Akgol, Gurkan (Georg Thieme Verlag Kg, 2023)
Aim We aimed to examine the effect of kinesiophobia on functional capacity, disease activity, quality of life and spatiotemporal parameters of patients with AS by comparing AS patients with healthy controls.Material and method Our study included 46 patients with ankylosing spondylitis (AS) and 45 healthy controls (HC). Bath Ankylosing Spondylitis Metrology Index (BASMI), Bath Ankylosing Spondylitis Functional Index (BASFI), Ankylosing Spondylitis Quality of Life Scale (ASQoL), Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), Tampa Kinesiophobia Scale (TKS) scores, Timed Up and Go (TUG) test, maximum plantar pressure and spatiotemporal parameters (total weight transfer, step cycle duration, double-support phase, swing phase, step length, foot angle and cadence) were evaluated.Results Ninety-one individuals (46 AS, 45 HC) (age/sex/BMI) were included in our study. Statistically significant differences were seen between AS and HC groups in TUG, cadence, TKS, maximum pressure, step cycle duration, swing phase, step length, double-support phase, and foot angle measurements (p<0.05). Significant positive correlations existed between TKS and BASMI, BASDAI, BASFI, ASoQ, TUG and foot angle (p<0.05) in AS. Substantial negative correlations were found between TKS and maximum pressure, cadence and swing phase values (p<0.05) in AS.Conclusion Our study is the first in the literature to measure spatiotemporal parameters between patients with AS and HC and evaluate their relationship with kinesiophobia, which was done to the best of our knowledge. We found that patients with AS changed their gait phases by developing a unique pattern and created a more cautious and safe gait model to provide balance and stability. Our study revealed a statistically significant relationship between kinesiophobia and disease activity, functional status, quality of life, cadence, maximum plantar pressure, swing phase, and foot angle. The detailed data we obtained in our study will shed light on gait analysis and research on kinesiophobia in patients with AS. Kinesiophobia should be evaluated in routine gait rehabilitation protocols applied to individuals with AS, and treatment protocols for kinesiophobia should be added if necessary.
Beeinflusst Kinesiophobie Raumzeitliche Parameter bei Patienten mit Ankylosierender Spondylitis?
Keywords: Ankylosing spondylitis; spatiotemporal parameters; kinesiophobia; TUG; BASFI